Drone Control using the Coupling of the PID Controller and Genetic Algorithm - Mohamed Elajrami; Zouaoui Satla; Kouider Bendine (Communications - Scientific letters of the University of Zilina, 2021)
Due to their strong abilities and easy usage, unmanned aerial vehicles (UAVs) commonly named drones have found a place and merged in the different industrial sectors. These varieties of applications encourage researchers to search for new control algorithms that make drones operate smoothly. In this regard, the present study mains to design a PID controller for four motors drones (quadcopter). For this purpose, a state-space representation of the drone is proposed based on Newton Euler’s formularies for a rigid body. For better performance of the control algorithm (PID) the parameters Kp, Ki, and Kd for the controller are established using an optimization search schema based on a genetic algorithm. Various simulations were performed to test the proposed idea.